Incidence of risk factors for bloodstream infections in patients with major burns receiving intensive care: A retrospective single-center cohort study. Issue 4 (June 2018) - Fochtmann-Frana, Alexandra; Freystätter, Christian; Vorstandlechner, Vera; Barth, André; Bolliger, Michael; Presterl, Elisabeth; Ihra, Gerald; Muschitz, Gabriela; Mittlboeck, Martina; Makristathis, Athanasios; Rath, Thomas; Radtke, Christine; et al.
Highlights: Most common isolates were Enterococcus sp., Candida sp. and Pseudomonas sp. A greater TBSA and ABSI were associated with a higher incidence of BSIs. The incidence of multidrug resistant (MDR) pathogens was relatively low. MDR gram-negative BSI isolates were associated with increased mortality. Burn patients from abroad often suffered from BSI caused by MDR bacteria. Abstract: Objectives: The objective was primarily to identify risk factors for bloodstream infections (BSI) caused by different pathogens. Methods: A retrospective single-center cohort study was performed on 472 burn patients with an abbreviated burn severity index (ABSI) ≥ 3, a total burn surface area (TBSA) ≥ 10%, and an ICU stay of at least 24 h. Risk factors for different BSI pathogens were analyzed by competing risks regression model of Fine and Gray. Results: A total of 114 burn patients developed 171 episodes of BSIs caused by gram-negative bacteria (n = 78;46%), gram-positive bacteria (n = 69;40%), and fungi (n = 24;14%) median after 14 days (range, 1–164), 16 days (range, 1–170), and 16 days (range, 0–89), respectively. A total of 24/114 patients (21%) had fatal outcomes. Isolation of the most common bloodstream isolates Enterococcus sp. (n = 26), followed by Candida sp. and Pseudomonas sp. (n = 22 for both) was significantly associated with increased TBSA (p ≤ 0.006) and ABSI (p < 0.0001) and need for fasciotomy (p < 0.01). The death risk of patients with MDR gram-negative bacteremia was significantly increased by a hazard ratio of 12.6 (95% CI:4.8–32.8; p < 0.0001). Conclusions: A greater TBSA and ABSI were associated with a significantly higher incidence of BSIs caused by Pseudomonas sp., Enterococcus sp. and Candida sp.